Star Wars ABC. ([New York] : Scholastic, 2010)
"An alphabetical adventure through the imaginative and intergalactic world of Star Wars featuring the names and images of the most popular characters, droids, spaceships, and creatures in this galaxy far, far away"--Publisher.
Title from cover.
On board pages.
"Lucas Books"--P. [4] of cover.
Keywords: Star Wars films -- Juvenile fiction; Alphabet books; Board books; Star Wars films -- Fiction; Alphabet